Inflation and hyperinflation in Venezuela (1970s-2016): A post-Keynesian interpretation - Marta Kulesza (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2017)
This paper aims to explain the causes of rapidly increasing prices in Venezuela and establish whether the current episode can be considered to be of hyperinflationary nature from the post-Keynesian theoretical approach. The chosen approach highlights the role of distributive conflict, indexation mechanism, balance of payments constraint, devaluation expectations and gradual rejection of national currency in favour of foreign currency. We argue that the root cause of the precarious economic situation in Venezuela lies in the long term failure to implement structural changes, ensuring industrial diversification and lessening the dependency on oil exports. The symptoms of the Dutch disease are observed in the prolonged currency overvaluation during the high oil revenue periods. In the face of a growing external constraint, the authorities introduce severe foreign currency rationing. This in turn ignites inflation due to external bottlenecks since many sectors face supply constraints as they depend on imports of inputs of production. This leads to a regressive distribution of income, which contributes to the growing distributive conflict and fuels inflation further, as workers oppose to the lowering of real wages. Moreover, the currency rationing puts pressure on the black market for exchange as the devaluation expectations increase, leading to a parallel market devaluation-inflation spiral, which threatens to turn into hyperinflation. Nevertheless, we argue that hyperinflation, according to the proposed post-Keynesian framework (the flight to foreign currency), does not materialise despite skyrocketing prices because of the particular institutional setting - the exchange controls, which have been in place since 2003, prevent full currency substitution.
Keywords: E12; E31; O54; 330; hyperinflation; foreign exchange; distributive conflict; expectations; Dutch disease; Venezuela